The quest for sustained growth : Southeast Asian and Southeast European cases - Wells, Samuel F.; Hager, Barry M.; ... [et al.] (Woodrow Wilson Center Press ; Distributed by the Johns Hopkins University Press, 1999)
Introduction. The crisis and transition in Southeast Europe and Southeast Asia. The rise and fall of emerging markets. The IMF and economic sovereignty...